Estimating Marginal Propensities to Consume in Australia Using Micro Data - Chung, L; McKibbin, R; Berger-Thomson, L (My University, 2009)
This paper uses micro data from the Household, Income and Labour Dynamics in Australia Survey to estimate the marginal propensity to consume. Estimates are made by examining two types of policy changes – to income tax rates and lump-sum transfers – which help to identify the effect of shocks to income on consumption. A standard Euler equation for consumption is used to analyse the effect of income tax changes. The marginal propensity to consume out of lump-sum transfers is estimated using fixed effects and propensity score matching. In addition, the paper examines differences in the marginal propensity to consume across households according to measures of liquidity constraints and unemployment risks.
Reserve bank of Australia Discussion Paper
Research Discussion Papers
Keywords: Finance; Finance -- Expenditure and constraints on expenditure; Income, wealth and finances; Finance; Expenditure and constraints on expenditure; Income, wealth and finance